EFFICIENCY OF METHODS OF FIGHTING RESPIRATORY DISEASES OF CALVES IN “BAYSERKE-AGRO” LLP - Egorova Natalia Nikolaevna; Sushchikh Vladislava Yuryevna; Ivanov Nikolai Petrovich; Namet Aidar Myrzakhmetuly; Aliyev Murat Ashrafovich (Scientific Journal of Pedagogy and Economics, 2019)
The article presents the results of clinical and epizootological data, bacteriological and serological studies of biological material from sick calves. As a result of bacteriological examination of feces samples from 3 calves (inv. № 7022, inv. № 70420, inv. № 7886) with clinical signs of salmonellosis (bronchopneumonia, increased body temperature, general depression, lack of appetite, characteristic posture with drooping neck), received for research in 2016, calf salmonellosis pathogen was isolated from fecal samples from all calves Salmonella dublin. 3 cultures isolated from calf feces were identical in their cultural-morphological, tinctorial, antigenic and pathogenic properties. Based on the study of the biological properties of the culture identified as S. dublin. Specific Salmonella antibodies were recorded in the serum of sick calves in RA with salmonella antigen. As a result of science-based veterinary-sanitary and preventive measures in the economy, salmonellosis of calves was eliminated. There were no cases of outbreaks of salmonellosis among calves on the farm, which indicates the effectiveness of methods to control salmonellosis of calves at “Bayserke-Agro” LLP.